Estudo da dinâmica de portadores em diodos de tunelamento ressonante tipo-p - Galeti, Helder Vinicius Avanço (Universidade Federal de São Carlos, 2007)
Photoluminescence spectroscopy has been used to provide important insight on the tunneling dynamics of carriers in double barrier diodes. In this work, we have performed time-resolved photoluminescence measurements in symmetric and asymmetric p-type GaAs/AlAs resonant tunneling diodes in order to study the tunneling dynamics of photocreated minority electrons. We observed several peaks in the current voltage characteristics (I-V) associated to the resonant tunneling of holes through different quantum well heavy- and light-hole sub-bands. Under light excitation, we have observed the developing of additional peaks in the I-V curve. For the asymmetric structure, two peaks were observed and associated to the exciton assisted tunneling and resonant tunneling of photogenerated electrons. We have studied the temporal evolution of the GaAs contact and quantum well (QW) emission versus the applied bias voltage. For the QW, the luminescence comes solely from the recombination between the lowest-energy confined levels in the QW even when the device is biased at higher tunneling resonance peaks. For both structure, the PL decay depends on the applied voltage and presents a bi-exponential decay for some values of bias. The results revealed a markedly long PL decay at the bias voltage associated the exciton assisted tunneling resonance in the current voltage characteristic. For the GaAs emission, we observed a weak dependence of the PL intensity versus voltage and a mono-exponential decay. We analyze our results considering the diffusion and tunneling of minority electrons in the structure
Keywords: Tunelamento (Física); Luminescência; Heteroestruturas; Poços quânticos; Propriedades ópticas; CIENCIAS EXATAS E DA TERRA::FISICA